Safety and Tolerability of a Wearable, Vibrotactile Stimulation Device for Parkinson’s Disease - Tabacof, Laura; Braren, Stephen; Patterson, Taylor; Fry, Adam; Putrino, David (Frontiers in Human Neuroscience, 2021)
Background: Resting tremor is a cardinal symptom of Parkinson’s Disease (PD) that contributes to the physical, emotional and economic burden of the disease. Objective: The goal of this study was to investigate the safety, tolerability and preliminary effectiveness of a novel wearable vibrotactile stimulation device on resting tremor in individuals with PD. Methods: Using a randomized cross-over design, subjects received two different vibrotactile stimulation paradigms (high amplitude patterned and low amplitude continuous) on two separate laboratory visits. On each visit, resting tremor was video recorded for 10 minutes at baseline and while the vibrotactile stimulation was applied. Tremor severity was scored by a blinded clinician. Results: Both vibration paradigms were well safe and well tolerated and resulted in a reduction in resting tremor severity with a moderate effect size (n=44, P<0.001, r=0.37-0.54). There was no significant difference between the two vibration paradigms (P=0.14). Conclusions: Short durations of vibrotactile stimulation delivered via wearable devices were safe and well tolerated and may attenuate resting tremor severity in individuals with PD. The sample size as well as the potential preliminary effectiveness revealed by two arms of the study could not eliminate the potential for a placebo effect.